Association of dietary patterns with diabetes complications among type 2 diabetes patients in Gaza Strip, Palestine: a cross sectional study - Abdel Hamid el Bilbeisi; Saeed Hosseini; Kurosh Djafarian (BMC, 2017)
Abstract Background The prevalence of diabetes mellitus is rising worldwide. When diabetes is uncontrolled, it has dire consequences for health and well-being. However, the role of diet in the origin of diabetes complications is not understood well. This study identifies major dietary patterns among type 2 diabetes patients and its association with diabetes complications in Gaza Strip, Palestine. Methods This cross sectional study was conducted among 1200 previously diagnosed type 2 diabetes mellitus (both genders, aged 20-64 years), patients receiving care in primary healthcare centers in Gaza Strip, Palestine. Dietary patterns were evaluated using a validated semi-quantitative food frequency questionnaire. Additional information regarding demographic and medical history variables was obtained with an interview-based questionnaire. Statistical analysis was performed using SPSS version 20. Results Two major dietary patterns were identified by factor analysis: Asian-like pattern and sweet-soft drinks-snacks pattern. After adjustment for confounding variables, patients in the lowest tertile of the Asian-like pattern characterized by a high intake of whole grains, potatoes, beans, legumes, vegetables, tomatoes and fruit had a lower odds for (High BP, kidney problems, heart problems, extremities problems and neurological problems), (OR 0.710 CI 95% (.506-.997)), (OR 0.834 CI 95% (.700-.994)), (OR 0.730 CI 95% (.596-.895)), (OR 0.763 CI 95% (.667-.871)) and (OR 0.773 CI 95% (.602-.991)) respectively, (P value <0.05 for all). No significant association was found between the sweet-soft drinks snacks pattern with diabetes complications. Conclusion The Asian-like pattern may be associated with a lower prevalence of diabetes complications among type 2 diabetes patients.